PENGEMBANGAN SILABUS PEMBELAJARAN BAHASA INGGRIS BERWAWASAN EKOWISATA PADA KAMPUNG INGGRIS BERBASIS WISATA NEGERI SAWAI MALUKU TENGAH - Tuanany, Nur Laila (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2022)
This study aims to develop a syllabus of English language learning with an ecotourism perspective in a Tourism-Based English Village in Sawai, North Seram District, Central Maluku Regency. The development research carried out is intended to find out the learning syllabus used in tourism-based English villages in Sawai at this time, obtain data and conclusions about the syllabus used, compile and develop a syllabus that emphasizes the concept of ecotourism according to the needs of students in Kampung Inggris Sawai, obtaining the validity of test results from material, syllabus and curriculum experts, obtaining field test results on the syllabus that has been developed, and obtaining the feasibility results of the syllabus. The method used in this study is Research and Development (R&D). The syllabus development model uses procedures developed by Yalden, namely needs analysis, description of goals, selection of syllabus type development, making proto syllabus, making learning syllabuses, as well as evaluations that include validation from experts and trial stages. The syllabus that has been developed covers topics related to the concept of ecotourism in Sawai, namely environment, Asinahu River, Enjoy Your Stay, Weather and Season, Marine Tourism, Beach Watersport, Transportation, The Beauty of Ora, The Love Pond of Bubara Fish, The Hatupia Cliff, Natural Resources, Festivals in Sawai, Ecotourism, and Local Wisdom. Keywords: English Syllabus, Ecotourism, Sawai, Development